2015
DOI: 10.15403/jgld.2014.1121.243.abo
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Volatile Organic Compounds Emitted from Faeces for the Diagnosis of Giardiasis

Abstract: Background: Giardiasis is a common intestinal infection caused by the flagellated intestinal protozoan Giardia duodenalis. Several methods are available for the laboratory diagnosis of Giardia, ranging from the microscopic identification of the parasite trophozoite and cyst stages, to immunodiagnosis and PCR. Giardia has unique metabolic pathways resulting from its lack of mitochondria, making it an ideal target for volatile organic compound (VOC) profiling. Aim: To characterise the VOC profile of stool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Using a variety of methods and substrates, other studies have suggested a utility of volatile organic compound analysis for the diagnosis of GI disease, including colorectal cancer. One such study, from 2015, used selected ion flow tube mass spectrometry to analysis volatile organic compounds emitted from faeces of FOBt positive patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a variety of methods and substrates, other studies have suggested a utility of volatile organic compound analysis for the diagnosis of GI disease, including colorectal cancer. One such study, from 2015, used selected ion flow tube mass spectrometry to analysis volatile organic compounds emitted from faeces of FOBt positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mass spectrometer was run in electron impact (EI) ionisation mode, scanning the mass ion range 10‐300 at 0.05 scan/s. A 4 minute solvent delay was used at the start of the run …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…G . lamblia is a parasitic protozoan dwelling in the small intestine of human and mammal animals and causes giardiasis [ 21 ]. Due to the importance of gut-associated lymphoid tissue (GALT) in the immune response to enteric pathogens, a ideal vaccine against gastro-intestinal pathogens should be able to access GALT through mucosal M cells located predominantly in the Peyer’s patches (PP) and therefore activate mucosal defenses in the intestinal tract [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fecal VOCs might be a useful group among intestinal metabolites in the regulation of metabolic homeostasis. Interestingly, fecal VOC analysis was performed to evaluate the pathological features of gastrointestinal diseases [18][19][20] including inflammatory bowel disease (IBD) [21][22][23] , irritable bowel syndrome 21,24 , Crohn's disease 25 , colorectal cancer (CRC) 26,27 , and necrotizing enterocolitis 28,29 , as well as infectious diseases including paratuberculosis [30][31][32][33][34] , sepsis 35 , giardiasis 36 , and Clostridium difficile infection 37 . However, it is difficult to handle intestinal microbial VOCs, because of their unpleasant odor, gaseous form, and low boiling point resulting in their loss when using general sample preparation methods including evaporation or concentration.…”
mentioning
confidence: 99%